An Exploratory Study on the Adoption and Use of ICT in Myanmar - LAU, Sim Kim (Institutional Knowledge at Singapore Management University, 2013)
This exploratory study investigates the adoption and use of information and communication technologies in Myanmar by examining the nature and structure of the information technology profession. The investigation is based on a theoretical framework consisting of three components: domains of information technology professional expertise; the scope of the information technology professional’s knowledge, skills and experience; and specific knowledge and skills associated with the domains of professional expertise. The findings show that specialist skills in systems development, database, network and communications are important. This paper also provides insights that are not found in current literature which investigates information technology skills in Myanmar.